HEAT WAVES, AGING, AND HUMAN CARDIOVASCULAR HEALTH - Kenney, W. Larry (2014)
This brief review is based on a President’s Lecture presented at the Annual Meeting of the American College of Sports Medicine in 2013. The purpose of this review is to assess the effects of climate change and consequent increases in environmental heat stress on the aging cardiovascular system. The earth’s average global temperature is slowly but consistently increasing, and along with mean temperature changes come increases in heat wave frequency and severity. Extreme passive thermal stress resulting from prolonged elevations in ambient temperature, as well as prolonged physical activity in hot environments, creates a high demand on the left ventricle to pump blood to the skin to dissipate heat. Even healthy aging is accompanied by altered cardiovascular function, which limits the extent to which older individuals can maintain stroke volume, increase cardiac output, and increase skin blood flow when exposed to environmental extremes. In the elderly, the increased cardiovascular demand during heat waves is often fatal due to increased strain on an already compromised left ventricle. Not surprisingly, excess deaths during heat waves 1) occur predominantly in older individuals and 2) are overwhelmingly cardiovascular in origin. Increasing frequency and severity of heat waves coupled with a rapidly growing at-risk population dramatically increases the extent of future untoward health outcomes.